Streptococcus salivarius Role as a Probiotic in Children’s Health and Disease Prophylaxis—A Systematic Review - Flavia Cristina Al-Akel; Lacramioara Eliza Chiperi; Vas Krisztina Eszter; Anca Bacârea (Life)
Background: This systematic review aimed to synthesize the existing evidence on the use of Streptococcus salivarius (S. salivarius) probiotics as prophylactic or therapeutic tools for pediatric oral, dental, and respiratory diseases. Methods: A comprehensive search was carried out across multiple databases using the following terms: S. salivarius, probiotic, children, pediatric. Results: The systematic literature search identified 613 publications, which were meticulously screened, and, ultimately, 15 suitable citations were included in this systematic review. Three strains of S. salivarius (M18, K-12, 24SMB) were used, and they all demonstrated positive benefits in pediatric pathology. Conclusions: Administration of S. salivarius has benefits, is effective, and is convenient (cost-effective) in pediatric prophylaxis. Oral administration as a chewable tablet or powder of S. salivarius M18 for 3 months is able to reduce the incidence of black stains, plaque, and tooth decay in children. S. salivarius K-12 treatment decreased the occurrence of pharyngeal, recurrent, and streptococcal disease, and the benefits also extend to a reduction of nonstreptococcal diseases, including tracheitis, viral pharyngitis, rhinitis, flu, laryngitis, acute otitis media, and enteritis. Administration of S. salivarius 24SMB as an intranasal spray was able to reduce the risk of acute otitis media in children prone to this condition.